Influence of the Sampling Area on the Chemical, Physical, and Mechanical Properties of Grewia bicolor(GB) Fiber for Potential Use in the Reinforcement of Tannin Matrix Composites - MICHEL MBERE TAOGA; Fabien Betene Ebanda; Antonio Pizzi; Benoit Ndiwe; Pierre Marcel Anicet Noah; Jonas Peequeur Essome Mbang; Kevin Kibong Kimbi; Etinge Tabi Akwo; César Segovia (Journal of Natural Fibers)
The aim of this study is to chemically, physically, and mechanically characterize Grewia bicolor (GB) fibers harvested in the NGONG locality located in the North Cameroon region for potential use in the elaboration of tannin matrix composites. The fibers are extracted from three zones of the stem (top (T), middle (M), and bottom (B)) by biological retting with stagnant water, and the various standard norms are respected for different tests. Analysis by Fourier transform infrared spectroscopy (FTIR) and chemical composition show that GB fibers consist mainly of cellulose (50.73–53.67%), hemicellulose (20.95–24.73%), and lignin (14.26–17.26%). Physical properties give: true density (1.33–1.35 g/cm3), bulk density (0.61–0.72 g/cm3), porosity (48.37–51.4%), linear density (17.28–29.44 tex), water content (13.16–13.59%), water absorption rate (121.86–134.54%), and a moisture recovery rate at 75% relative humidity (11.12–11.76%). Mechanical parameters give Young’s modulus (17.21–29.56 GPa), stress at break (504.71–936.09 MPa), and strain at break (4.65–5.37%). Analysis of variance (ANOVA) combined with Tukey’s test for mechanical properties show that the bottom and middle fibers are identical at the 95% confidence level. GB fibers can be used in the reinforcement of tannin matrix composites with preferable and indiscriminate sampling in the bottom and middle zones of the stem.